On Art and Artists : The Video Data Bank. (Chicago : Video Data Bank, 1982)
Akerman, Chantal ; Anderson, Laurie ; Antin, Eleanor ; Aycock, Alice ; Baldessari, John ; Bartlett, Jennifer ; Bengston, Billy Al ; Beuys, Joseph ; Bourgeois, Louise ; Brakhage, Stan ; etc.
Engels
boek